FFECTIVE VALUE OF SWIMMING INSTRUCTION COMPARED WITH THE STUDENTS' QUALIFYING EXAM - Jovica Tošić; Milomir Trivun; Simo Vuković; Željko Panić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The survey was performed among the male students of second year from the Faculty of Physical Education and Sports at the University of East Sarajevo. A comparison of the swimming at the beginning and at the end of the Winter Semester was made, with the result success of qualifying entrance examination during the admission at the Faculty of Physical Education and Sports. The total sample of respondents consisted of 31 students of the Faculty of Physical Education and Sports. The sample of variables was related to the result success in swimming in 50 meters freestyle (crawl technique).The results both with the descriptive comparative analysis of the central tendency measures (minimum, maximum, mean value) and with t-test indicate the effective values of swimming instruction compared with the qualifying entrance examination student admission at the Faculty of Physical Education and Sports